EXPERIENCE OPTIMIZATION PROCESS IN TERMS OF EXPLOSION - , А. А., С. А., А. Б., Б. И. (Municipal economy of cities (Technical science), 2013)
At the simplest example, we optimize the methodology parameters (capacity of two different attitudes toward the two different substances) process equipment to reduce the explosion of the enterprise.